2001
DOI: 10.1523/jneurosci.21-22-08734.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increased Seizure Susceptibility in Mice Lacking Metabotropic Glutamate Receptor 7

Abstract: To study the role of mGlu7 receptors (mGluR7), we used homologous recombination to generate mice lacking this metabotropic receptor subtype (mGluR7 Ϫ/Ϫ ). After the serendipitous discovery of a sensory stimulus-evoked epileptic phenotype, we tested two convulsant drugs, pentylenetetrazole (PTZ) and bicuculline. In animals aged 12 weeks and older, subthreshold doses of these drugs induced seizures in mGluR7 Ϫ/Ϫ , but not in mGluR7 ϩ/Ϫ , mice. PTZ-induced seizures were inhibited by three standard anticonvulsant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 85 publications
(104 reference statements)
7
158
0
2
Order By: Relevance
“…Spontaneous mutations causing epilepsy are not known in mice or in humans; however, mice in which GluR7 has been deleted by gene targeting show an in-creased susceptibility to seizures and increased cortical excitability. 289 Acquired forms of epilepsy show marked changes in the expression and function of mGluRs. In the kindling model of epilepsy, there is upregulation of group I receptors that can be demonstrated by biochemical or electrophysiological functional assays.…”
Section: Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Spontaneous mutations causing epilepsy are not known in mice or in humans; however, mice in which GluR7 has been deleted by gene targeting show an in-creased susceptibility to seizures and increased cortical excitability. 289 Acquired forms of epilepsy show marked changes in the expression and function of mGluRs. In the kindling model of epilepsy, there is upregulation of group I receptors that can be demonstrated by biochemical or electrophysiological functional assays.…”
Section: Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…37 We have validated a method for siRNA-induced knockdown in the mouse. 16 As many of the initial studies of mGluR7 have relied on information from mGluR7 knockout animals, 10,12,38,39 which are bred on a C57BL/6 background, we chose to conduct our siRNA studies on this background. Seventy-four male C57BL/6 mice (23-31 g; Charles River, France) were housed and surgeries performed as described previously, 15 40 ).…”
Section: Cta Following Amn082mentioning
confidence: 99%
“…mGluR7 À/À mice were generated as described previously from E14 (129/Ola) embryonic stem cells (Sansig et al, 2001). Larger age-matched groups of mGluR7 À/À and mGluR7 + / + mice were generated using a specific pathogen-free (SPF) breeding colony of 30 F14, B6-mGluR7 + /À males mating with 60-90 F14, B6-mGluR7 + /À females.…”
Section: Animalsmentioning
confidence: 99%
“…Mice lacking mGluR7 have deficits in amygdala-dependent behaviors (fear response and conditioned taste aversion), but show no alterations in locomotor activity or pain sensitivity (Masugi et al, 1999). Electrophysiological analysis in mGluR7 À/À mice further suggests that this receptor is a frequency-dependent regulator of neurotransmitter release (Sansig et al, 2001), and modulates short-term synaptic plasticity in the hippocampus (Bushell et al, 2002). Moreover, we have demonstrated that mGluR7 ablation in mice is associated with changes in animal behavioral paradigms predictive of antidepressant and anxiolytic action, which suggests that drugs acting at mGluR7 may provide novel treatments for psychiatric disorders such as depression and anxiety (Cryan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%